Toxicity test of mangosteen peel extract (Garcinia mangostana L.) as denture cleanser of heat-cured acrylic resin: in vitro experimental laboratory - Tertya, Bertha Bening; Kristiana, Dewi; Naini, Amiyatun (Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: Mangosteen peel extract can be used as a denture cleaning agent to effectively inhibit the growth of C. albicans because mangosteen peel contains various compounds such as mangostin, tannins, flavonoids, saponins. Denture cleaning materials that will be used in the dental field must meet biocompatibility requirements, one of which is a toxicity test. The aim of this study was to analyze the toxicity of mangosteen peel extract as a cleaner of heat cured acrylic resin denture on BHK-21 as cell culture of fibroblast cells. Methods: Toxicity test used the MTT assay method. Acrylic resin samples had a diameter of 3 mm and a thickness of 2 mm. The acrylic resin was soaked for 4 days, equivalent to soaking 15 minutes per day for 1 year in mangosteen peel extract with concentrations of 50, 60, 70%, and sodium hypochlorite. Analyzed data using normality and homogeneity test results showed (p<0.05). Kruskal Wallis test results (0.000<0.05) and Mann Whitney (0.000<0.05). Results: The greatest cell viability value was shown in mangosteen peel extract with a concentration of 50%, namely 97.16939%. Based on research data, it can be said that the lower the concentration of mangosteen peel extract, the lower the level of toxicity of a denture cleanser agent. Mangosteen peel extract in concentrations of 60, 70%, and sodium hypochlorite are toxic when used as a denture cleanser. Conclusion: Mangosteen peel extract with a concentration of 50% is not toxic to BHK-21 fibroblast cells as cell culture of and as a cleaner of heat cured acrylic resin denture on.Keywordheat-cured acrylic resin, mangosteen peel extract, MTT assay.